In the Best Interest of the Child: the Norwegian Approach to Child Protection - Melinder, Annika; van der Hagen, Malin Albrechtsen; Sandberg, Kirsten (International journal on child maltreatment : research, policy and practice, 2021)
In the present paper, we discuss three challenges with the Norwegian Child Protective System (CPS) that might have contributed to the recent criticism from the European Court of Human Rights (ECtHR). First, how to balance the rights of the child with those of the parents. Second, the psychological field’s influence on the interpretation of what constitutes the best interest of the child, and third we describe several missing links in the CPS work. Throughout the paper, we find indications of a well-developed Act, but a less optional CPS practice. Likewise, we find evidence for a narrow interpretation of the best interest of the child related to CPS and expert psychologists’ application of attachment theory, and several organizational and educational shortcomings in the area of CPS. We conclude that the child is not fully seen as a legal subject in the eyes of the ECtHR, and that more research into CPS measures and organization are needed to better deliver adequate assistance to vulnerable families.